Effects of new beta-type Ti-40Nb implant materials, brain-derived neurotrophic factor, acetylcholine and nicotine on human mesenchymal stem cells of osteoporotic and non osteoporotic donors - Kauschke, Vivien; Gebert, Annett; Calin, Mariana; Eckert, Jürgen; Scheich, Sebastian; Heiss, Christian; Lips, Katrin Susanne; Justus Liebig University Giessen (My University, 2018)
Introduction: Treatment of osteoporotic fractures is still challenging and an urgent need exists for new materials, better adapted to osteoporotic bone by adjusted Youngs modulus, appropriate surface modification and pharmaceuticals.Materials and methods: Titanium-40-niobium alloys, mechanically ground or additionally etched and titanium-6-aluminium-4-vanadium were analyzed in combination with brain-derived neurotrophic factor, acetylcholine and nicotine to determine their effects on human mesenchymal stem cells in vitro over 21 days using lactate dehydrogenase and alkaline phosphatase assays, live cell imaging and immunofluorescence microscopy.Results: Cell number of human mesenchymal stem cells of osteoporotic donors was increased after 14 d in presence of ground titanium-40-niobium or titanium-6-aluminium-4-vanadium, together with brain-derived neurotrophic factor. Cell number of human mesenchymal stem cells of non osteoporotic donors increased after 21 d in presence of titanium-6-aluminium-4-vanadium without pharmaceuticals. No significant increase was measured for ground or etched titanium-40-niobium after 21 d. Osteoblast differentiation of osteoporotic donors was significantly higher than in non osteoporotic donors after 21 d in presence of etched, ground titanium-40-niobium or titanium-6-aluminium-4-vanadium accompanied by all pharmaceuticals tested. In presence of all alloys tested brain-derived neurotrophic factor, acetylcholine and nicotine increased differentiation of cells of osteoporotic donors and accelerated it in non osteoporotic donors.Conclusion: We conclude that ground titanium-40-niobium and brain-derived neurotrophic factor might be most suitable for subsequent in vivo testing.
Keywords: ddc:610